Letramentos acadêmicos em contexto de expansão do ensino superior no Brasil - Maria de Lourdes Santos Ferreira (2013)
Academic writing studies are strongly associated with the expansion of higher education in Brazil and in other parts of the world. Current higher education students profile changes can be especially noticed in academic writing, and demand discussion on the new teaching methodologies becoming a rich field for research (LILLIS, 1997, 2006; LILLIS & SCOTT, 2008; IVANIC, 1988; LEA & IVANIC, 2006; LEA & STREET, 1998; STREET, 1984, 2003, 2009). Effects of the expansion for literacy practices in Brazil are still little known mostly because it is a reality being experienced for less than a decade now (MARINHO, 2007, 2010; FIAD, 2011; CORREA, 2011). Considering this situation, the following research has as main objective understanding academic literacy, in the context of the expansion of higher education. In order to do so, the locus of observation has been a federal public university, situated at Jequitinhonha Valley, in the State of Minas Gerais, in Brazil, created in this context. Thus, having the conceptions of literacy such as skills, socialization and as a social practice (LEA & STREET, 1998) as threshold; this research presents three conceptions maps of the academic work aiming at understanding the concepts of literacy that support them. The research is essentially qualitative and considers as corpus for analysis a set of literacy events (HEATH, 1982, 1983; STREET, 2003), and adopt as a theoretical and methodological approaches the academic literacy, the Discourse Analysis and Textual Linguistics. The analyses led to the conclusion that there is heterogeneity in the context researched due to multiple factors, such as the expectation that the writing is present in different arenas. Another finding is that literacy practices constitute and are constituted in and by the academic relationship with the University, marking the specificity of each gender there produced along the way and the goals that this new university has as a new professional idealised.